The Michigan Autism Spectrum Questionnaire: A Rating Scale for High-Functioning Autism Spectrum Disorders. (5th December 2013) - Ghaziuddin, M.; Welch, K.
Abstract : Although the DSM-5 has recently created a single category of autism spectrum disorder (ASD), delineation of its putative subtypes remains clinically useful. For this process, screening instruments should ideally be brief, simple, and easily available. The aim of this study is to describe the validity of one such instrument. We administered the Michigan Autism Spectrum Questionnaire (MASQ), a 10-item questionnaire, to 42 patients with ASD (age range 6–13 years, mean 9.7 years, SD 2.5, one female) and 18 patients with other psychiatric disorders (age range 6–17 years, mean 11.7 years, SD 3.8, 6 females). Responses to each item were scored from 0 to 4 yielding a total score of 30. Patients with intellectual disability were excluded. As a group, patients with ASD scored higher than those with other psychiatric disorders (Chi-square test with 1 df = 16.019, P < 0.0001 ). Within the ASD group, a linear discriminant analysis found that the best cut-off points were 22 or above for Asperger syndrome, 14 to 21 for autism/PDDNOS, and less than 14 for those with other psychiatric disorders. We propose that the MASQ can be used as a brief measure to screen high-functioning ASD from other psychiatric disorders and to identify its possible subtypes.